2013
DOI: 10.1371/journal.pone.0069072
|View full text |Cite
|
Sign up to set email alerts
|

The Apgar Score and Infant Mortality

Abstract: ObjectiveTo evaluate if the Apgar score remains pertinent in contemporary practice after more than 50 years of wide use, and to assess the value of the Apgar score in predicting infant survival, expanding from the neonatal to the post-neonatal period.MethodsThe U.S. linked live birth and infant death dataset was used, which included 25,168,052 singleton births and 768,305 twin births. The outcome of interest was infant death within 1 year after birth. Cox proportional hazard-model was used to estimate risk rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 17 publications
6
110
1
6
Order By: Relevance
“…There was a statistically significant association between a baby's Apgar score and child survival. This corroborates findings from the study by Li et al [26], which found a relationship between five-minute Apgar scores and infant survival. In their study, the Apgar score showed its predictive value for infant death of both very preterm, preterm, and term infants in postneonatal period.…”
Section: Neonatal Factorssupporting
confidence: 92%
“…There was a statistically significant association between a baby's Apgar score and child survival. This corroborates findings from the study by Li et al [26], which found a relationship between five-minute Apgar scores and infant survival. In their study, the Apgar score showed its predictive value for infant death of both very preterm, preterm, and term infants in postneonatal period.…”
Section: Neonatal Factorssupporting
confidence: 92%
“…The net effect of a low Apgar score at 5 minutes on the relative risk of both neonatal and infant mortality is thereby smaller for premature infants than observed at term. Although the Apgar score is associated with mortality at all gestations [5][6][7]20 , the magnitude of the effect changes across the distribution of gestational ages because the background mortality risk of each gestational group varies. Hence, a normal score in preterm infants, unlike full term infants, does not necessarily predict a good outcome 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar associations were reported in a single centre study of 151,891 singletons from 1988-1998 5 . A more recent population study utilising US birth registry data from 1995-2004, also reported increased crude mortality rates among term and pre-term infants with low Apgar scores at 5 minutes 6 . Importantly, however, none of these studies adjusted for known risk factors for mortality including birthweight, social class, smoking status or previous neonatal death.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…A 5-minute Apgar score of 0 to 3 correlates with neonatal mortality in large populations 11,12 but does not predict individual future neurologic dysfunction. Population studies have uniformly reassured us that most infants with low Apgar scores will not develop cerebral palsy.…”
Section: Prediction Of Outcomementioning
confidence: 96%